Characteristics and speciation of heavy metals in fly ash and FGD gypsum from Chinese coal-fired power plants. (1st September 2019) - Fu, Biao; Liu, Guijian; Mian, Md. Manik; Sun, Mei; Wu, Dun
Highlights: The petrology, mineralogy, and chemistry of fly ashes were comparatively studied. The ratio of oxidizable bound elements in CFB ash is higher than in PC ash. The mobile fractions of Cr, Cu, Zn, and As were notably higher in FGD gypsums. Heavy metals in all gypsums show a medium risk or high risk to the ecosystem. Abstract: This research focused on the distribution and chemical speciation of Cr, Pb, Cd, Cu, Zn, and As in fly ash and flue gas desulfurization gypsum (FGD gypsum) from a large-scale pulverized coal-fired (PC) power plants in Anhui Province of eastern China. The partitioning behavior of the heavy metals (HMs) revealed that trace metals were mainly retained in coal combustion ash (88.9–98.7%) and FGD gypsum (1.26–4.33%). Other fly ashes generated from different PC boilers and a circulated fluidized boiler (CFB) were collected to comparatively study the ash mineralogy and chemistry. The PC fly ashes were dominated by glassy materials including cenospheres, pleiospheres, ferrospheres, solid spheres, and Fe-bearing spinel, while irregular glassy particles and unburned carbon were observed in the CFB ashes. The results of SEM-EDS found that PC ash mainly consisted of <100-µm-diameter aluminosilicate spherical particles. In contrast, CFB ash was primarily comprised of fine irregular Al-Si-Ca-O agglomerates. FGD gypsums, occurring as large flaky crystals, were primarily composed of CaSO4 ·2H2 O with minor quartz and calcite. According to the sequential chemical extraction procedure, the amount of HMs occurring as oxidizable associations of fluidized ash was higher than that of PC ash, which might be associated with the lower flame temperature in CFB boiler. The percentage of Cr (43.1–53.2%), Cu (79–87.8%), Zn (67.8–89.6%), and As (64.5–75.6%) as effective fraction was notably higher in FGD gypsums compared with fly ashes. The leaching tests revealed that all combustion residues were non-hazardous materials. The RACs (risk assessment codes) of Cr, Pb, Cd, and As in fly ashes indicated that they posed no risk or low risk to the ecosystem, while the HMs in all FGD gypsums showed a medium risk or high risk to the ecosystem. Therefore, the reuse of FGD gypsums should be carefully evaluated since the environmental stability of HMs in gypsums was weaker compared with fly ashes.